The Participation of Indonesia in Regional Fisheries Management Organizations (RFMOs): The Legal and Globalization Perspectives - Aryuni Yuliantiningsih (Universitas Kuningan, 2019)
Abstract : The purpose of this research is to find out and analyse the participation of Indonesia in Regional Fisheries Management Organizations (RFMOs) viewed from the legal and globalization perspectives. The method used in this research was a normative juridical by employing secondary data sources which were analysed qualitatively. The results showed that there are 4 (four) RFMOs bordering Indonesian waters, namely IOCT, CCSBT, WPPC, and Inter-American Tropical Tuna Commission (IATTC). Currently, Indonesia has participated as a member of RFMOs with the reasons, firstly, to participate in conserving fish resources and secondly, if Indonesia is not a member of RFMOs, the fishery products can be embargoed and categorized as IUU fishing. In relation to law and globalization, developed countries have implemented their hegemony to dominate the high seas through legal instruments, namely international treaties and organizations. On the other hand, the participation of Indonesia in RFMO is merely to facilitate the citizens to be able to access fish resources in the high seas.Keywords: Indonesia, RFMOs, law, globalization. Keikutsertaan Indonesia dalam Regional Fisheries Management Organizations (RFMOs): Perspektif Hukum dan Globalisasi Tujuan penelitian ini untuk mengetahui dan menganalisis keikutsertaan Indonesia dalam Regional Fisheries Management Organizatios (RFMOs) ditinjau dari perspektif hukum dan globalisasi. Metode penelitian yang digunakan adalah yuridis normatif, menggunakan sumber data sekunder dan analisis dilakukan secara kualitatif. Hasil penelitian yaitu terdapat 4 (empat) RFMOs yang berbatasan dengan perairan Indonesia yaitu, IOCT, CCSBT, WPPC, Inter-American Tropical Tuna Commission (IATTC). Saat ini Indonesia telah ikut serta menjadi anggota RFMOs dengan alasan, pertama, ikut melakukan konservasi sumber daya ikan dan kedua, jika tidak menjadi anggota RFMOs maka hasil tangkapan dapat diembargo dan dikategorikan sebagai IUU fishing. Dikaitkan dengan hukum dan globalisasi, negara maju telah menerapkan hegemoninya untuk menguasai laut lepas melalui instrumen hukum yaitu perjanjian internasional dan organisasi internasional. Di sisi lain keikutsertaan Indonesia dalam RFMO untuk memfasilitasi warga negaranya agar dapat mengakses sumberdaya ikan di laut lepas.Kata Kunci: Indonesia, RFMOs, hukum, globalisasi.